Modelling the effect of copper on the growth rate of Enterobacter sp. strain Neni-13 on SDS - Rusnam; Gusmanizar, Neni; Shukor, M. Y.; Dan-Iya, Bilal Ibrahim (Hibiscus Publisher, 2021)
The introduction of tiny amounts of heavy metals into the environment can encourage the growth of a wide variety of microorganisms. The concentration at which enhanced microbial activity is seen, on the other hand, results in a significant decrease in growth rate as well as an increase in lag time (due to the higher lag time). An established link exists between heavy metal toxicity in microorganisms and the process of bioremediation, which has been well-documented. Because heavy metals have an impact on bioremediation, they must be researched, and appropriate countermeasures must be implemented. Copper reduced the growth of the SDS-degrading bacteria Enterobacter sp. strain Neni-13 to a significant extent. Under varying doses of mercury, the SDS-degrading bacteria exhibited a sigmoidal pattern with time periods ranging from 7 to 10 hours. Gompertz's model was used to calculate the growth rates of copper in different concentrations. As the copper concentration rose, the growth of bacteria was suppressed with a concentration of 1.0 g/L, with virtually total stoppage of bacterial development. From the Gompertz model, we got the estimates of growth rates; after which, they were estimated according to the Han-Levenspiel, Shukor, Wang, Liu, Andrews, and Amor models. The modified Han-Levenspiel, Andrews, Liu, and Shukor models could all successfully fit the curve. Results of the statistical analysis showed that the Han-Levenspiel model was the best model based on highest adjusted correlation coefficient (adR2), the lowest values for RMSE and AICc, and values of AF and BF closest to unity. The parameters obtained from the Han-Levenspiel model were Ccrit 0.209 mg/L (95%, C.I., 0.199 to 0.219), Î¼max 0.209 h-1 (95% C.I., 0.199 to 0.219) and m 0.472 (95% C.I., 0.383 to 0.561. The results obtained in this study indicate the maximum tolerable copper concentration that the conditions for biodegradation should not exceed.